Comparison of Color Enhancement Efficacy in the Ornamental Cichlid Protomelas similis between Using CAROPHYLL® pink, Mangosteens Pericarp Crude Extract, and 17α-methyltestosterone Hormone - Sirimanapong, Wanna; Phatcharawannatat, Krittiya; Thiengtrong, Klar; Chincharoendee, Dusita; Kijpraiboon, Supatta; Jongkolpath, Oranee (Journal of Mahanakorn Veterinary Medicine, 2020)
The aim of this experiment was study the efficacy of color enhancement mangosteen pericarp crude extract, color enhancing CAROPHYLL® pink and 17α-methyltestosterone hormone on color skin of Protomelas similis. The experimental design was a Completely Randomized Design (CRD) of 6 treatments follow as types of supplementation feed for color enhancement in P. similis (control feed, feed supplement with CAROPHYLL® pink, mangosteen pericarp crude extract, 17α-methyltestosterone hormone, 17α-methyltestosterone hormone plus CAROPHYLL® pink and 17α-methyltestosterone hormone plus mangosteen pericarp crude extract). P. similis were fed by these feeding program and then were evaluated color scoring by expert who had experience about cichlid contests. From this study, found that the different color enhancing feed groups had significantly effect on P. similis skin color (P<0.05) which P. similis that were fed 2 times a day for 10days by 17α-methyltestosterone hormone plus CAROPHYLL® pink had highest color score. However, P. similis were fed with mangosteen pericarp crude extract didn’t show different color enhancing feed groups compared to the control group within 10 days (P>0.05). The combination between 17α-methyltestosterone hormone and CAROPHYLL® pink in the feed help to P. similis express skin color in short term.